The Devil Within: Reflections on Sex/Gener Identities in the Light of Story a Trans - Contreras-Salinas, S; Ramirez-Pavelic, M (UNIV AUTONOMA CIUDAD MEXICO, 2023)
The objective of the research is to identify the main elements that come together in the conformation of the identity of a male transsexual subject. A qualitative research design is used for this, through case study and thematic content analysis. Six categories merge from the results: difference, transit, specialists, confusion, name and anger. From the analysis of Victor s discourse, the adoption of cultural prejudices and normalizing psychological models, which would mostly be at the service of the hegemonic power, can be seen. It concludes in the urgency of collecting the approaches of critical psychology, in order to deconstruct and reconstruct the concept of diversity.